The practice of science and religion integration: Evidence from an Indonesian Islamic school - Jailan Sahil; Siti Zubaidah; Aloysius Duran Corebima; Abdul Gofur; Muhammad Saefi (University of Muhammadiyah Malang, 2024)
This paper answers the call for the importance of integrating the Islamic worldview into science classes. This research provides insights into science teachers' experiences of integrating science and Islam, as well as additional surveys to reveal gains in student understanding. This research consists of two stages. Study 1 used phenomenology and focused on the voice of science teachers through focus groups. This research involved five focus groups in five Islamic high schools providing information describing their experiences. Through thematic analysis techniques, several findings were obtained as follows: (1) the concept of integration emphasises more on the balance of compliance between vertical and horizontal; (2) the integration pattern places more emphasis on learning materials; and (3) in terms of benefits, this effort is focused on increasing understanding and followed by study 2 which aims to add to the evidence base by investigating the effect of integration patterns on student understanding. The results showed that there is evidence that the support of an overarching integration pattern contributes to students' understanding of the material. As a recommendation, it is necessary to strengthen integration at all stages of science learning, allowing students to take advantage of discussions in class to develop more relevant abilities.